Analisis Pengaruh Covid-19 Dan Pembatasan Sosial Berskala Besar (PSBB) Terhadap Fluktuasi IHSG - Halwa Annisa Khoiri; Wildanul Isnaini (Pusat Publikasi Ilmiah LPPM Institut Teknologi Sepuluh Nopember, 2022)
Covid-19 is a global disaster that affects various aspects, one of which has an impact on the economy. One of the indicators of economic stability is the Jakarta Composite Index (JCI). During the Covid-19 pandemic, the JCI fluctuated because many investors withdrew their money and switched to safe heaven investment. One example of safe heaven investment is gold, so in this study, the prediktort variables used were the price of gold, the rupiah exchange rate, the number of Covid-19 patients, and the status of the PSBB. The PSBB status used is the implementation of PSBB in DKI Jakarta using three periods, namely, pre-PSBB, PSBB, and post-PSBB (new normal era). Based on the results of the analysis, the variables that significantly influence the fluctuation of the JCI are all prediktort variables with a R 2 value of 71.1%. So it can be concluded that the model formed is suitable for predicting the JCI value, as well as the selected prediktort variables, can explain the variation of the JCI by 71.1%. From this significant variable, it can also be used as an alternative in investment during a pandemic like now.